High live coral cover and incidence of a pink-spotted coral phenotype on remote reefs off Clipperton Island, Tropical Eastern Pacific - Pogoreutz, Claudia; Clua, Eric E. G.; Tortolero-Langarica, J. J. Adolfo (Marine biology, 2022)
Clipperton, an uninhabited and remote coral atoll from the Eastern Pacific, is an important steppingstone area that harbors a high marine biodiversity. Despite its biogeographic importance, little information on the ecological status of its coral reefs is available from the last decade. Herein, we characterized the benthic coral community and health status among four different shallow reef-zones (North to South) of Clipperton during the Tara Pacific expedition in 2018. The benthic composition (expressed as coverage percentage), as well as occurrence of potential disease-like phenotypes, in particular a pink-spotted coral phenotype was assessed. Average live coral cover on Clipperton reefs was 66% (range 55–85%), differing between sites, with massive Porites and branching Pocillopora corals dominating the benthic community with an average 48% (32–66%), and 15% (3–21%), respectively. While Clipperton reefs exhibited significant live coral cover overall, and no other disease-like phenotypic were observed, the pink-spotted coral phenotype was common, with a higher occurrence in massive corals ( Porites 27%, and Pavona 31%). This observation may be related to the combined effects of previously heatwaves, and local inputs of guano-derived nutrients discharged during storms and hurricanes, which may suggest that even highly remote reefs supporting high coral cover can be subject to local and global threats. An alternative hypothesis is that the observation of a healthy reef with high coral cover and high incidence of pink-spotted coral phenotype in the absence of other diseases might reflect potential infection with the parasitic trematode Podocotyloides stenometra . While this hypothesis will have to be confirmed by histological and molecular analysis, it may be possible that larvae of this trematode may experience favorable conditions due to periodic nutrient input frorm the nutrient-rich lagoon or via guano run-off of Clipperton Island.